J.H. Johnston, Revised Charter and Ordinances of the City of Boonville, Mo. 91, No. 17, art. 1, § 6 (1881) - (:unkn) unknown (General Publisher, 1881)
Prohibited concealed carry of any pistol, revolver, dirk, dagger, slungshot, metallic knuckles, or other deadly or dangerous weaponor exhibit in a rude, angry, or threatening manner, or carry any such weapon while intoxicated. . Violators fined not less than five but no more than ninety dollars.
--
Keywords: CARRY - CONCEALED